Design and Analysis of Synchronverter based Virtual Inertia Control for Hybrid Power Plants - Osama Bin Muzaffar (00000204892); Dr Abasin Ulasyar (USPCAS-E, NUST, Islamabad, 2021)
TH-279
Keywords: MS-ESE Thesis